Progressive limit state at critical levels of internal potential energy of deformation - Leonid Yu. Stupishin (Moscow State University of Civil Engineering (MGSU), 2021)
Introduction. The work is devoted to one of the main issues of structural mechanics - the determination of the elements in which the limiting state occurs first. At first glance, the task has an infinite number of results, meaning an infinite number of options for loading the system. The problem becomes solvable if one examines the structure of a building (structure) for possible variations in displacements (forces) in the nodes of the structure. For this approach, it becomes possible to determine the main values and vectors of displacement of the system, which correspond to the maximum (minimum) values of deformations (forces) in the rods of the system. As close approaches to the formulation of the problem, one should indicate the theory of the limiting equilibrium of structures under the assumption of the work of the material under flow conditions, where the equality of the work of external forces and internal forces is considered (kinematic method), or possible static stress states of the system for maximum limiting loads (static method). The theory of protecting buildings and structures from progressive collapse seeks to solve similar problems, focusing on options for design solutions that prevent destruction from non-design loads.